Membangun Karakter dan Pola Pikir Islami melalui Strategi Pembelajaran Kontekstual di Mata Pelajaran PAI (Penelitian di Sekolah SMP Al-Ma’arif Cipicung Kabupaten Tasikmalaya) - Yanto Maulana Restu; Inriyani Inriyani; Dapid Ahmad Pahrija; Dede Rifa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine the extent to which the Contextual Teaching and Learning (CTL) strategy contributes to character building and the development of Islamic thinking among students through Islamic Religious Education (PAI) lessons at Al-Ma'arif Cipicung Junior High School, Tasikmalaya Regency. This study is based on empirical evidence that PAI teaching practices in schools are often positioned as the delivery of normative and conceptual material, so that the religious values taught are not fully realized in the attitudes and behavior of students in their daily lives. To uncover this phenomenon, this study uses a qualitative approach by combining observation techniques, in-depth interviews, and documentation analysis as the main sources of data collection. The findings show that the application of CTL in PAI learning is able to create a more participatory learning process, deepen religious understanding that is relevant to the context of students' lives, and encourage the internalization of Islamic values in social interactions and daily practices. Linking PAI material to students' concrete experiences has proven effective in fostering religious character, such as honesty, a sense of responsibility, and social awareness, while also developing a critical and reflective Islamic mindset. However, this study also notes several obstacles, including the continued strong reliance on lecture methods and the lack of student engagement. Keywords: contextual learning, Islamic religious education, Islamic character